2010
DOI: 10.1007/s10658-010-9632-y
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic investigations in the downy mildew genus Bremia reveal several distinct lineages and a species with a presumably exceptional wide host range

Abstract: Bremia lactucae is one of the most devastating and widespread pathogens in lettuce production worldwide. Despite its economical importance, uncertainty prevails about the species delimitation in the genus Bremia. Commonly, Bremia is considered to be monotypic, containing only Bremia lactucae, while taxonomists have described additional species, and molecular phylogenetic studies have shown significant sequence divergence between accessions from different hosts. Here, we report that several previously described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
3
16
0
Order By: Relevance
“…Based on sequence analysis of D1/D2/D3 region in 28S ribosomal DNA (rDNA), Riethm€ uller et al (2002) and Voglmayr et al (2004) have first provided an important molecular evidence for the presence of distinct entities within B. lactucae, and later Choi et al (2007b) showed a high degree of sequence heterogeneity in the internal transcribed spacer 2 (ITS2) rDNA of the species complex. Recently, Thines et al (2010) have demonstrated the distinctiveness of some species of Bremia described from Europe, but were not providing morphological data for the species investigated. Thus, the possibility to distinguish species of Bremia has been still unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…Based on sequence analysis of D1/D2/D3 region in 28S ribosomal DNA (rDNA), Riethm€ uller et al (2002) and Voglmayr et al (2004) have first provided an important molecular evidence for the presence of distinct entities within B. lactucae, and later Choi et al (2007b) showed a high degree of sequence heterogeneity in the internal transcribed spacer 2 (ITS2) rDNA of the species complex. Recently, Thines et al (2010) have demonstrated the distinctiveness of some species of Bremia described from Europe, but were not providing morphological data for the species investigated. Thus, the possibility to distinguish species of Bremia has been still unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is great uncertainty as to the number of species that are actually involved, and current species estimates of the genus Peronospora range from 75 to c. 400 (Voglmayr 2003), depending on the species concept applied. Recent molecular phylogenetic investigations clearly show that the species biodiversity of downy mildews in general, and Peronospora in particular, is higher than commonly perceived (e.g., Choi et al 2007aChoi et al , b, 2009Choi et al , 2011aGarcía Blázquez et al 2008;Göker et al 2004Göker et al , 2009Rouxel et al 2013;Runge et al 2011;Schröder et al 2011;Thines 2011;Thines and Kummer 2013;Thines et al 2009bThines et al , 2010Voglmayr 2003Voglmayr , 2008Voglmayr and Göker 2011;Voglmayr et al 2014a, b), and appears to be correlated with high host specificity triggering speciation as well as little morphological differentiation between related species (cryptic speciation). Therefore, it is not surprising that several new Peronospora species have been detected Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For inferring tree robustness, 1,000 bootstrap replicates (Felsenstein 1985) were carried out. Bayesian Analysis was done using MrBayes (Huelsenbeck and Ronquist 2001), version 3.12, as detailed in Thines et al (2010). For maximum likelihood inference (Felsenstein 1981), RAxML (Stamatakis 2006) in the latest version implemented on the server at CIPRIS (http://8ball.…”
Section: Alignments and Phylogenetic Inferencementioning
confidence: 99%